2004
DOI: 10.1111/j.1365-2141.2004.04904.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical evaluation of a LightCyclerTM‐mediated polymerase chain reaction assay, a nested‐PCR assay and a galactomannan enzyme‐linked immunosorbent assay for detection of invasive aspergillosis in neutropenic cancer patients and haematological stem cell transplant recipients

Abstract: Summary Invasive aspergillosis (IA) is a considerable clinical problem in neutropenic patients with haematological malignancies but its diagnosis remains difficult. We prospectively evaluated a LightCyclerTM polymerase chain reaction (PCR) assay, a nested‐PCR assay and a galactomannan (GM) enzyme‐linked immunosorbent assay (ELISA) to validate their significance in diagnosing IA. During 205 treatment episodes in 165 patients from six centres, a nested‐PCR assay and GM testing was performed at regular intervals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 33 publications
5
84
1
2
Order By: Relevance
“…On the other hand, since fungi are ubiquitous in the environment, panfungal PCR methods are more likely to yield contaminated products, while the use of specific probes will reduce this possibility [13,20]. Sensitivity will probably improve if amplification is achieved by nested PCR [13,19], although some reports have showed similar sensitivity results [26] to ours. Sensitivity will also improve by using real-time PCR [26].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…On the other hand, since fungi are ubiquitous in the environment, panfungal PCR methods are more likely to yield contaminated products, while the use of specific probes will reduce this possibility [13,20]. Sensitivity will probably improve if amplification is achieved by nested PCR [13,19], although some reports have showed similar sensitivity results [26] to ours. Sensitivity will also improve by using real-time PCR [26].…”
Section: Discussioncontrasting
confidence: 41%
“…Although the procedure is easy to perform, the sensitivity of the assay was quite low (75%) compared to some published data [19,26]. However, in these reports, only IA was screened.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, there have been several reports of antifungal treatment being associated with conversion of PCR test results from positive to negative. 18,31,32 These findings may partly explain the many single positive PCR tests for Candida in this study, as many of these patients received prophylaxis with fluconazole. However, the single positive PCR tests for Aspergillus are difficult to explain because only 4 of these 15 patients received active treatment or prophylaxis against Aspergillus.…”
Section: Discussionmentioning
confidence: 76%
“…This finding is consistent with earlier reports in which a single positive PCR test did not correlate with proven or probable fungal disease and resolved without treatment. 31,32 One possible explanation is laboratory contamination that is hard to eliminate even though extensive precautions were used. Another possible reason for false positive Aspergillus PCR was recently reported to be contaminated nutritional supplement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have reported variable sensitivity (range, 30 -90%) and specificity (range, 89 -97%) with the GM assay. [12][13][14][15] In studies comparing GM with PCR, Buchheidt et al 16 reported that PCR had a sensitivity of 63% compared with 33% for GM. The specificity of PCR was 63%, compared with 98% for enzyme immunoassay.…”
Section: Discussionmentioning
confidence: 99%